PENGARUH LATIHAN PLYOMETRIK MELOMPATI KUN DENGAN DUA KAKI KE SAMPING, SECARA ZIG-ZAG PADA SISWA PUTRA KELAS VIII A - Amrizal, Amrizal; Siska, Siska (Jurnal Ilmu Keolahragaan Undiksha, 2020)
This study aims to determine whether there is 1) The effect of plyometric training jumping over a kun with two legs to the side, 2) The effect of the plyometric training jumping over a kun with two legs in a zig-zag manner, 3) Comparison of the plyometric exercise jumping over a kun with two legs sideways and in a zig-zag manner on leg muscle power for male students of class VIII A SMP Negeri 1 Rambah, Rokan Hulu Regency. This type of research is a quasi experiment. The population was all male students of class VIII A SMP Negeri 1 Rambah, Rokan Hulu Regency, totaling 12 people. The sampling technique used in this study was total sampling, namely the entire population of male students of class VIII A SMP Negeri 1 Rambah, Rokan Hulu Regency. The instrument used in collecting data was the Standing Broad Jump test. The data analysis technique used was the t-test, where 1) The effect of the plyometric training jumping over a kun with two legs to the side is 4.27, 2) The effect of the plyometric training jumping over a kun with two legs in a zigzag manner is 5.97, 3) Comparison plyometric exercise jumping kun with two legs to the side and zigzag the leg muscle power of male students class VIII A SMP Negeri 1 Rambah, Rokan Hulu Regency is 2.36 with t table is 1.81. So from the two exercises given there are significant differences.